Criminal Liability for a Private Party in Outer Space - Lapienytė, Kristina; Prakopaitė, Meda (Vilnius University Open Series, 2024)
This article analyses whether a private party can be a subject of a criminal deed, since till now this issue has not been exhaustively consolidated either in the legal acts of the Republic of Lithuania nor foreign countries, therefore a necessity arises to ensure that there are no gaps in law that could determine the fact that criminal law would not fulfil a protective function, in other words, the interests of the individual, the society and the state would not be secured. The article evaluates where the limit is, when space law comes into force and analyzes the legal regulation of outer space. Future problems related to space tourism are revealed and the problem of committing a criminal offence in outer space is assessed. The analysis carried out in this work shows that the issues of criminal jurisdiction and criminal liability for a private party is quite problematic, as the provisions of many significant international agreements are unclear and differently evaluated. However, the aforementioned problematic issues can be resolved based on the systematic application of legal sources.